The Implications of Islamic Law Related to the Implementation of CashWaqf /Money - Muchtar Anshary Hamid Labetubun; La Ode Angga (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
. Cash Waqf is a term that is becoming familiar in today's society, because Cash Waqf usually refers to cash deposits in financial institutions such as banks, where Cash Waqf is usually invested in profitable business activities, profits from the investment results are used for everything that is socially and religiously useful. The purposes of this research to analize Cash Waqf that is carried out by a person, group of people, and institutions or legal entities in the form of cash/money. Also included in the interpretation of money are securities, such as shares, checks, and others. The method used in this study was normative juridical for analyzing legal issues contained in legislation related to the problem under study with qualitative analysis. The results showed that endowments in the form of cash are permissible as long as the money is invested in a business for results (Mudharabah), after which the profits are distributed according to the endowments. So that the money represented is always, on the contrary, what is informed to the mauquf ‘alaih is the result of developing the endowment of the money. However, there are several main challenges in developing the potential of Cash Waqf in Indonesia in addition to governance challenges, including the low literacy of the Indonesian people about Cash Waqf and limited financial instruments in developing the value (assets) of Cash Waqf.